PERAN AGAMA SEBAGAI PENGUAT INTEGRITAS APARATUR SIPIL NEGARA (ASN) DALAM MEMBERANTAS KORUPSI DI INDONESIA - Tjahyo Rawinarno (LPPM STIA Banten, 2022)
Background of this research is declined of Indonesia rank at Global Corruption Perception Index. There is a data that shown how Public Servant Procurement highest coruppted on public sector level. So, it must be an ethic on governance. Theories that be used as guidance are according from Organization for Economic Cooperation and Development (OECD), which is focus on three infrastructur Guidance, Control, and Management. Research methode that used is descriptive qualitative. Approaching by literature study from government and other resources that relevant. The result that revelead of religion value not yet implemented. Therefore, strenghten of public servant integrity before nation ideology.